(Ny side: [https://www.matematikk.net/matteprat/viewtopic.php?f=13&t=48351 Diskusjon av oppgaven på matteprat])
 
Linje 1: Linje 1:
 
[https://www.matematikk.net/matteprat/viewtopic.php?f=13&t=48351 Diskusjon av oppgaven på matteprat]
 
[https://www.matematikk.net/matteprat/viewtopic.php?f=13&t=48351 Diskusjon av oppgaven på matteprat]
 +
 +
=DEL 1=
 +
 +
==Oppgave 1==
 +
 +
===a)===
 +
 +
$f(x)=e^{2x} // f'(x)=2e^{2x}$
 +
 +
===b)===
 +
 +
$g(x)=\frac{x^4-1}{x^2} // g'(x)=\frac{4x^3 \cdot x^2 - (x^4-1) \cdot 2x }{(x^2)^2} // =\frac{4x^5-2x^5+2x}{x^4} // =\frac{2x^5+2x}{x^4} // = \frac{2x^4+2}{x^3}$
 +
 +
===c)===

Revisjonen fra 17. mar 2019 kl. 15:33

Diskusjon av oppgaven på matteprat

Innhold

DEL 1

Oppgave 1

a)

$f(x)=e^{2x} // f'(x)=2e^{2x}$

b)

$g(x)=\frac{x^4-1}{x^2} // g'(x)=\frac{4x^3 \cdot x^2 - (x^4-1) \cdot 2x }{(x^2)^2} // =\frac{4x^5-2x^5+2x}{x^4} // =\frac{2x^5+2x}{x^4} // = \frac{2x^4+2}{x^3}$

c)